Optimal operation of a residential district-level combined photovoltaic/natural gas power and cooling system. (15th October 2015) - Ondeck, Abigail D.; Edgar, Thomas F.; Baldea, Michael
Highlights: Study feasibility of a CHP plant with PV integration in a hot climate. Demand data collected from large-scale smart grid demonstration site. CHP plant model based on existing operating facility. CHP with district cooling can meet residential neighborhood energy demand in the Southwest United States. Abstract: Combined heat and power (CHP) facilities are a very promising path to reducing CO2 emissions and increasing efficiency in the power generation sector. The ability to supply essential residential utilities (electricity, cooling, and heating) in an efficient manner opens the way for combining district cooling, heating and power generation, and suggests that CHP plants are an attractive choice for providing integrated utilities for the neighborhood of the future. In this paper, we describe the optimal integration of a CHP plant as a utility producer for a residential district, and the potential for combining CHP with photovoltaic power generation. Utilizing residential energy demand data collected by Pecan Street Research Inc., a smart-grid demonstration project in Austin, TX, residential heating, cooling, and electricity demand are analyzed and evaluated. These demands are then used to compute an optimal operating strategy for an integrated CHP/solar utility and the impact of photovoltaic generation on plant operation and operating profit is determined. We demonstrate that CHP is a viable means for providing district-level cooling, heating, and power to a residential district in a hot climate.